Zaznavanje sedanje in prihodnje vloge visokošolskih knjižnic: primer knjižnic Filozofske fakultete Univerze v Ljubljani - Žugelj, Urška (Knjižnica, 2004)
Throughout history libraries have had many different roles. They served as educational centres, manuscript transcriptors and collectors, places for study, places offering services, even museums and entertainment facilities, etc. Their quality depends on a number of different factors, e.g. quality of staff, and of services, as well as on environmental characteristics. The current development in the information and communication technology has an important impact on libraries functions and therefore demands their permanent adjustment. In this study the authors tried to find out how 171 students and librarians from the Faculty of Arts perceive the current and future roles of academic libraries. Following this, the questionnaire was prepared on the basis of the following domain facets: time frame, services, communication typeand type of material. As expected in the partitions of the three dimensional (Smallest Space Analysis) space three facets with ordered elementsappeared (two axial: time frame and material, and one modular: communication type) and one unordered with the polar role: services. With the exception of the service facet, all the other facets clearly revealed themselves.
Keywords: visokošolske knjižnice; zaznavanje; bibliotekarji; uporabniki